Population genetic structure of Epinephelus marginatus in the Central Mediterranean Sea (Gulf of Gabe¨s and the coast of Libya) - Elglid, Aziza; Crouau-Roy, Brigitte; Bradai, Mohamed Nejmeddine; Fadhlaoui-Zid, Karima (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
In the present study, mitochondrial DNA sequences from the cytochrome b (cytb) gene and seven nuclear microsatellites were examined to assess the genetic diversity of Epinephelus marginatus inhabiting Tunisian and Libyan coastal waters. Based on 940 base pairs of the cytochrome b segment, we found low level of genetic variability for the two samples analysed (h = 0.294 ± 0.097and h = 0.274± 0.142 respectively in Tunisia and Libya). An analysis of molecular variance (AMOVA) showed significant pattern of genetic structure based on nuclear data (7 microsatellite loci) (Î¦ST= 0.28487; P < 0.001). Conversely, no genetic structuring was found for mtDNA (Î¦ST = -0.0121). In summary, this study provides preliminary assessment of geographical patterns of differentiation of E. marginatus in this region for conservation, management and stock identification.